Drug release profiles of modified MCM-41 with superparamagnetic behavior correlated with the employed synthesis method - Cuello, Natalia Inés (2017)
Mesoporous materials with superparamagnetic properties were successfully synthesized by two different methods: direct incorporation (DI) and wet impregnation (WI). The synthetized solids were evaluated as host of drugs for delivery systems and their physicochemical properties were characterized by XRD, ICP, N2 adsorption-desorption, spectroscopies of UV–Vis DR, FT-IR and their magnetic properties were measured. Indomethacin (IND) was incorporated into the materials and the kinetic of the release profiles was studied by applying the Pepas and Sahlin model. In this sense, materials modified by DI, particularly that with hydrothermal treatment, showed the higher adsorption capacity and slower release rate. This behavior could be associated to the synthesis method used that allowed a high percentage of silanol groups available in the solids surface, which can interact with the IND molecule. This feature coupled with the superparamagnetic behavior; make these materials very interesting for drug delivery systems.